Progress of Research on Diffuse Axonal Injury after Traumatic Brain Injury - Junwei Ma; Kai Zhang; Zhimin Wang; Gang Chen (Neural Plasticity)
The current work reviews the concept, pathological mechanism, and process of diagnosing of DAI. The pathological mechanism underlying DAI is complicated, including axonal breakage caused by axonal retraction balls, discontinued protein transport along the axonal axis, calcium influx, and calpain-mediated hydrolysis of structural protein, degradation of axonal cytoskeleton network, the changes of transport proteins such as amyloid precursor protein, and changes of glia cells. Based on the above pathological mechanism, the diagnosis of DAI is usually made using methods such as CT, traditional and new MRI, biochemical markers, and neuropsychological assessment. This review provides a basis in literature for further investigation and discusses the pathological mechanism. It may also facilitate improvement of the accuracy of diagnosis for DAI, which may come to play a critical role in breaking through the bottleneck of the clinical treatment of DAI and improving the survival and quality of life of patients through clear understanding of pathological mechanisms and accurate diagnosis.